2018
DOI: 10.3390/app8091437
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on the Application of the Steel Tube Slab Structure in Construction of a Subway Station

Abstract: It is an effective approach to use Steel Tube Slab (STS) structure combined with the Pile-Beam-Arch (PBA) method to construct a large-space underground station. Traditional construction methods cannot meet the requirement of construction because of the complicated soil layers and high building densities in urban areas. The STS method can effectively increase the rigidity of the supporting system by using steel tubes. Firstly, the stress of bolts and steel tubes are investigated in the construction process base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…However, for the numerical simulation software, c = 0 may cause some options to hardly perform, even the calculation of non-convergence. Therefore, the cohesions of sandy soils are generally assumed to be 1 kPa in the numerical analysis [37][38][39]. The segment is deemed to have a liner-elastic behavior, and the main mechanical parameters of the structure are shown in Table 5.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…However, for the numerical simulation software, c = 0 may cause some options to hardly perform, even the calculation of non-convergence. Therefore, the cohesions of sandy soils are generally assumed to be 1 kPa in the numerical analysis [37][38][39]. The segment is deemed to have a liner-elastic behavior, and the main mechanical parameters of the structure are shown in Table 5.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Accordingly, the field can be classified into five layers based on the mechanical properties and formation lithology, as shown in table 8. And the soil profile was shown in figure 17 [6].
Figure 17.Geological profile of the soil.
…”
Section: Description Of Engineering Project In Chinamentioning
confidence: 99%
“…A full three-dimensional model of the station construction was established using FLAC 3D software (FLAC 3D 5.0). The dimensions of the numerical model were 120 × 39 × 50 m to eliminate the boundary conditions [6], as shown in figure 20. The bottom of the model was fixed in X -, Y- and Z -directions.…”
Section: Numerical Modelling Of Engineering Applicationmentioning
confidence: 99%
“…Wu et al [11] proposed a new supporting method of shallow buried super-span tunnel based on small tunnel sheds. Jia et al [12] demonstrated that using a steel-tube-slab structure combined with the pile-beam-arch method is an effective approach when constructing a super-span underground station. Some scholars also focused on the selection of the excavation methods.…”
Section: Introductionmentioning
confidence: 99%